2010
DOI: 10.1016/j.vaccine.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Protection against pneumonic plague following oral immunization with a non-replicating vaccine

Abstract: Yersinia pestis is a dangerous bacterial pathogen that when inhaled can rapidly induce fatal pneumonic plague. Thus, there is a need for stable, safe, and easily administered mucosal vaccines capable of eliciting effective protection against pulmonary Y. pestis infections. Cationic liposome–nucleic acid complexes (CLDC) have been shown previously to be effective vaccine adjuvants for parenteral immunization, but have not been previously evaluated for use in oral immunization. Therefore, we investigated the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…For example, we have recently reported that oral administration of CLDC-adjuvanted vaccines is also capable of generating substantial protective immunity against pulmonary challenge with Yersinia pestis [87]. Thus, induction of efficient mucosal immunity, particularly at pulmonary surfaces, appears to be a general property of CLDC-based adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have recently reported that oral administration of CLDC-adjuvanted vaccines is also capable of generating substantial protective immunity against pulmonary challenge with Yersinia pestis [87]. Thus, induction of efficient mucosal immunity, particularly at pulmonary surfaces, appears to be a general property of CLDC-based adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…With a view to oral administration of the vaccine, the F1-V fusion has been expressed in transgenic plants and fruit and was demonstrated to be immunogenic by oral or sub-cutaneous delivery [70-72], and the expression of the F1 and V antigens by attenuated Salmonella strains dosed orally has been demonstrated to protect mice from bubonic plague [73,74]. Oral immunisation of mice with F1 and V antigens formulated in an amphipathic oily emulsion [75], or in cationic liposome-nucleic acid complexes (CLDC) combined with F1 antigen, has also been shown to protect mice partially or fully against pneumonic plague [76]. …”
Section: Prospects For Vaccinationmentioning
confidence: 99%
“…Microencapsulation (62) and lipid A mimetics (63) of recombinant LcrV–F1 fusion protein induced a mixed Th1/Th2 cell-mediated immune response and provided protection against pneumonic plague in mice and rats. Liposome, such as cationic liposome nucleic acid complexes (64), and proteosomes, such as protollin (65), have been evaluated with F1–LcrV and have been shown to protect against pneumonic plague.…”
Section: Role Of Molecular Adjuvantsmentioning
confidence: 99%